Loading and planform shape influence on the wing structural layout through topology optimization - Crescenti, Fabio; Kipouros, Timoleon; Savill, Mark (AIAA, 2018)
Topology optimization is a technique used to identify the optimal layout of a structure for a given objective and assigned boundary conditions. The progress it has experienced over the last three decades made it ready for industrial applications. In this paper topology optimization is employed to investigate the influence of sweep angle, aspect ratio and loading condition on the wing internal structure. The planform of the Common Research Model wing is used as a baseline. The geometry is modified parametrically to alter sweep angle and aspect ratio. Regarding the baseline planform, the optimization is performed considering the aerodynamic loading induced by the pull-up manoeuvre. Results are provided for AR=7 and AR=1, as well as sweep angle of 20 and 30 degrees. The results of topology optimization for all cases are compared. Common patterns are identified and exported to provide guidelines for the preliminary design of the wing primary structure.